CRITICAL DISCOURSE ANALYSIS ON FOREIGN MEDIA NEWS RELATED TO INVESTMENT SCAMS: AN ANALYSIS OF VAN DIJK' MODEL - Indrawan, Fani (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
Van Dijk's model of critical discourse analysis on foreign media news about These young Indonesians became rich through 'investment platforms'. They've now been charged with fraud. Van Dijk model consists of macrostructure, superstructure and microstructure. These three structures are used to analyze the discourse of the news text. The results of this research are: 1. The macrostructure of the text describes the theme of "investment fraud" in which there are some important points that are stated which refer back to the big theme; 2. The superstructure of the text explains the theme of the news and the scheme or order of news that is displayed in the news text. The theme or topic are found in the title, while the content and the closing of the news is found in the body of the text news; 3. The microstructure of the texts contain several elements of discourse, namely semantic aspects, syntactic aspects of stylistic aspects (lexicon) and rhetorical aspects (graphics, metaphors and expressions). The conclusion of this research confirms that Van Dijk model can be used to analyze the discourse of the news text by using critical discourse analysis.